Assessing disease activity of rheumatoid arthritis patients and drug-utilization patterns of biologic disease-modifying antirheumatic drugs in the Tuscany region, Italy - Convertino, Irma; Cazzato, Massimiliano; Tillati, Silvia; Giometto, Sabrina; Gini, Rosa; Valdiserra, Giulia; Cappello, Emiliano; Ferraro, Sara; Bonaso, Marco; Bartolini, Claudia; Paoletti, Olga; Lorenzoni, Valentina; et al. (Frontiers in Pharmacology, 2023)
To investigate the relationship between biologic Disease Modifying Anti-Rheumatic Drugs (DMARDs) initiation/discontinuations in rheumatoid arthritis (RA) patients identified in a healthcare administrative database (HAD) and Disease Activity Score 28 (DAS28) reported in the medical charts. This retrospective population-based study included RA first ever-biologic DMARD users accessing of the Pisa University Hospital from 2014 to 2016. Patients were followed up to until December 31 st , 2019. We evaluated the DAS28 recorded before (T0), after (T1) the biologic DMARD initiation, and before (TD0), after (TD1) discontinuations. Patients were classified "off-target" (DAS28>3.2) or "intarget" (DAS28≤3.2). We described the disease activity trends at initiation and discontinuations. Ninety-five users were included (73 females, mean age 59.6). Among 70 patients (74%) with at least three DAS28 measures, 28 (40.0%) were off-target at T0 and 38 (54.3%) in-target at T1. Thirty-three (47%) patients had at least one discontinuation, among those with at least three DAS28 assessments. In the disease activity trend, disease stability, or improvement was observed in 28 out of 37 (75.7%) patients at initiation and in 24 out of 37 (64.9%) discontinuations. Biologic DMARD discontinuations identified in HAD are frequently observed in situations of controlled RA disease. Further studies are warranted to confirm that these events can be used in HAD studies as proxies of treatment effectiveness.